The overlooked impact of rising glyphosate use on phosphorus loading in agricultural watersheds. Issue 1 (5th December 2018) - Hébert, Marie‐Pier; Fugère, Vincent; Gonzalez, Andrew
Abstract : Glyphosate is the most extensively used pesticide worldwide. In addition to raising ecotoxicological concerns, the use of glyphosate adds phosphorus (P) to agricultural landscapes, influencing the accumulation and cycling of P in soil and nearby surface waters. Yet pesticides have been largely ignored when monitoring anthropogenic sources of P in agricultural watersheds. Estimating the supply of P derived from glyphosate use, both globally and in the US alone, we show that trends have markedly increased over the past two decades. Across the US, mean inputs of glyphosate‐derived P increased from 1.6 kg P km −2 in 1993 to 9.4 kg P km −2 in 2014, with values frequently exceeding 20 kg P km −2 in areas planted with glyphosate‐resistant crops. Although still a minor source of P relative to fertilizers, P inputs from glyphosate use have now reached levels comparable to those from sources for which P regulations were initiated in the past. We thus argue for greater recognition of glyphosate's influence on P flow in watershed research and management.